The role of the defense attorney in the investigation (Journal of actual problems of jurisprudence, 2019)
This article discusses the activities of the defense attorney in the preliminary stages of investigation and trial, and examination of theoretical, legal and practical problems of the lawyer-defender in criminal proceedings, current problems in the activities of the defense attorney at this stage of the criminal process. Given proposals and recommendations for its improvement.Key words: the investigation, the preliminary investigation, law and freedom, a criminal trial, the defense attorney.